Rivaroxabananddabigatraninpatientsundergoing catheter ablation of atrial fibrillation - Morais, João (2014)
Aims: The recent availability of the novel oral anticoagulants (NOACs) may have led to a change in the anticoagulation regimens of patients referred to catheter ablation of atrial fibrillation (AF). Preliminary data exist concerning dabigatran, but information regarding the safety and efficacy of rivaroxaban in this setting is currently scarce. Methods: and results Of the 556 consecutive eligible patients (age 61.0 ± 9.6; 74.6% men; 61.2% paroxysmal AF) undergoing AF catheter ablation in our centre (October 2012 to September 2013) and enroled in a systematic standardized 30-day follow-up period: 192 patients were under vitamin K antagonists (VKAs), 188 under rivaroxaban, and 176 under dabigatran. Peri-procedural mortality and significant systemic or pulmonary thromboembolism (efficacy outcome), as well as bleeding events (safety outcome) during the 30 days following the ablation were evaluated according to anticoagulation regimen. During a 12-month time interval, the use of the NOACs in this population rose from <10 to 70%. Overall, the rate of events was low with no significant differences regarding: thrombo-embolic events in 1.3% (VKA 2.1%; rivaroxaban 1.1%; dabigatran 0.6%; P = 0.410); major bleeding in 2.3% (VKA 4.2%; rivaroxaban 1.6%; dabigatran 1.1%; P = 0.112), and minor bleeding 1.4% (VKA 2.1%; rivaroxaban 1.6%; dabigatran 0.6%; P = 0.464). No fatal events were observed. Conclusion: The use of the NOAC in patients undergoing catheter ablation of AF has rapidly evolved (seven-fold) over 1 year. These preliminary data suggest that rivaroxaban and dabigatran in the setting of catheter ablation of AF are efficient and safe, compared with the traditional VKA.